Adopter une approche écosystémique : accepter de changer - Nancy Tanguay; Johanne Saint-Charles; Sylvie de Grosbois (VertigO)
In order to address complex environmental problems, the recognition and integration of different sources of knowledge are often required. To do so, new approaches have been developed. The ecosystem approach to health is one such new way. It combines participatory research and transdisciplinarity and involves the meeting of multiple stakeholders that typically hold different perspectives but share a common interest. We used such an approach in the context of a research project aiming to find culturally relevant solutions to the issue of environmental contaminants and “traditional” food safety for the Atikamekw communities. It allowed us to question our scientific methods in order to maintain a dialogue between the different knowledge bases and reach a better understanding of the issue from the communities’ perspective.